Control Activities and its Impact on the Performance of Private Banks (Jaffna District) - Muraleetharan, P. (JUICE- 2012 University of Jaffna, 2012)
This study was undertaken with the objective of finding out the relationship between control activities and performance of the private banks in Jaffna District, SriLanka. The study is based on thirty employees in the organizations. Internal control and performance measured by chi square and regression analysis. The study finds control activities and performance are statistically significant in determining performance. Perhaps most importantly, the study finds positive relationship between control activities and performance. Further the study suggests that work performed by the organizations have been implemented in the past and the work schedules take into consideration the goals of internal control. The study further points out that keen attention should be paid on to adopt efficient management information system and training of the staff. All these enhance the staff productivity and reducing costs and also ensure the efficient operation of the firms and financial performance of their operation as well.
Keywords: Control Activities; Financial Performance; Market performance